Factores socioculturales modificantes de la identidad local en la comuna San José del cantón Santa Rosa, 2020 - Coyago Lavanda, Dayse Maribel; Encalada Maldonado, Julissa Sarita (Machala: Universidad Técnica de Machala, 2021)
Being part of the Technical University of Machala, Faculty of Social Sciences of the career of Sociology and Political Sciences, which is enrolled in the graduation option of Undergraduate Work, under the Integrative Project modality, which is based on the study of Modifying Sociocultural Factors of Local Identity in the San José district of Canton Santa Rosa, 2020. The modifying sociocultural factors of the local cultural identity would be related to the influence of the communication media such as technologies and migratory flows; For this reason it is important not to leave aside the true origin, history and sense of belonging. In addition, culture is the set of beliefs, customs and traditions that characterize a town, being transmitted from generation to generation, likewise cultural elements such as, dances, music, values and games have been part of the cultural integration of the commune and these manifestations throughout the life of the people have been modified due to social factors such as: migration, technology and globalization. The main objective of the research will be focused on determining the conditions of sociocultural metamorphosis in the population of San José of the Santa Rosa canton through the elaboration of the proposal to safeguard the cultural identity of the commune, to achieve this objective it is necessary to establish the types of manifestations that show the alteration of the cultural identity of the site and identify the sociocultural factors that underlie the modification of traditional sociocultural practices in the inhabitants of the place and determine the consequences that derive from the acculturation processes in the inhabitants of the commune . The research has a Rational Deductive approach that will be used for the development of the problem, addressing the analysis and study of the data obtained, with a qualitative research methodological approach, whose techniques are bibliographic to develop the theoretical variables and 30 interviews conducted among them teachers of the educational units, improvement committee and inhabitants of the commune, which will allow obtaining clear and precise information about the object of study based on the qualitative analysis of the data provided by the actors. On the other hand, the loss of cultural identity in the residents of the sector, where a series of sociocultural factors underlie that have led to the displacement of customs and traditions, therefore it is considered pertinent to carry out the research proposal based on the elaboration and publication of a document of experiential stories MEMORIES of the elderly in the San José commune where stories will be captured where the autochthonous culture of the commune is evidenced in order to keep their traditions, customs and local identity latent. The execution of the document of Living Stories MEMORIES of the elderly will help to strengthen the local identity, giving the inhabitants a sense of belonging, safeguarding the tangible and intangible cultural heritages of the San José commune, enhancing the indigenous culture of the site whose roots are they have been fading due to the sociocultural metamorphosis of the place.
Ser parte de la Universidad Técnica de Machala, Facultad de Ciencias Sociales de la carrera de Sociologia y Ciencias Políticas, que se inscribe en la opción de graduación de Trabajo de Titulación, bajo la modalidad Proyecto Integrador, el mismo que se basa en el estudio de los Factores Socioculturales Modificantes de la Identidad Local en la comuna San José del Cantón Santa Rosa, 2020. Los factores socioculturales modificantes de la identidad cultural local estarían relacionados a la influencia de los medios de comunicación como las tecnologías y los flujos migratorios, por ello es importante no dejar de lado el verdadero origen, historia y sentido de pertenencia. Además, la cultura es el conjunto de creencias, costumbres y tradiciones que caracterizan a un pueblo, siendo trasmitido de generación en generación, así mismo los elementos culturales como: bailes, músicas, valores y juegos han sido parte de la integración cultural de la comuna y estas manifestaciones a lo largo de la vida de las personas se han ido modificando debido a factores sociales como: migración, tecnología y la globalización. El objetivo principal de la investigación estará enfocado a determinar las condiciones de metamorfosis sociocultural en la población de San José del cantón Santa Rosa mediante la elaboración de la propuesta para salvaguardar la identidad cultural de la comuna, para lograr alcanzar este objetivo se requiere establecer los tipos de manifestaciones que evidencian la alteración de la identidad cultural del sitio e identificar los factores socioculturales que subyacen en la modificación de las prácticas socioculturales tradicionales en los habitantes del lugar y determinar las consecuencias que se derivan de los procesos de aculturación en los habitantes de la comuna. La investigación tiene un enfoque Racional Deductivo que serán utilizados para el desarrollo del problema, dirigiéndose al análisis y estudio de los datos obtenidos, con un enfoque metodológico de investigación cualitativo, cuya técnicas son bibliográfica para desarrollar las variables teóricas y 30 entrevistas realizadas entre ellos docentes de las unidades educativas, comité promejoras y habitantes de la comuna lo que permitirá obtener información clara y precisa acerca del objeto de estudio tomando como base el análisis cualitativo de los datos proporcionados por los actores. Por otro lado, la pérdida de identidad cultural en los moradores del sector, en donde subyacen una serie de factores socioculturales que han conllevado al desplazamiento de costumbres y tradiciones, por ende se considera pertinente la realización de la propuesta de la investigación basada en la elaboración y publicación de un documento de relatos vivenciales MEMORIAS de los adultos mayores de la comuna de San José donde se plasmarán historias en donde se evidencie la cultura autóctona de la comuna con el fin de mantener latente sus tradiciones, costumbres e identidad local. La ejecución del documento de Relatos vivénciales MEMORIAS de los adultos mayores ayudara a fortalecer la identidad local, dándole a los habitantes sentido de pertenencia salvaguardando los patrimonios culturales tangibles e intangibles de la comuna San José, realzando la cultura autóctona del sitio cuyas raíces se han venido desvaneciendo debido a la metamorfosis sociocultural del lugar.
Keywords: CULTURA; MODIFICANTE; IDENTIDAD; COMUNA